Asymmetry in the Farley‐Buneman dispersion relation caused by parallel electric fields. Issue 11 (11th November 2016) - Forsythe, Victoriya V.; Makarevich, Roman A.
Abstract: An implicit assumption utilized in studies of E region plasma waves generated by the Farley‐Buneman instability (FBI) is that the FBI dispersion relation and its solutions for the growth rate and phase velocity are perfectly symmetric with respect to the reversal of the wave propagation component parallel to the magnetic field. In the present study, a recently derived general dispersion relation that describes fundamental plasma instabilities in the lower ionosphere including FBI is considered and it is demonstrated that the dispersion relation is symmetric only for background electric fields that are perfectly perpendicular to the magnetic field. It is shown that parallel electric fields result in significant differences between the growth rates and phase velocities for propagation of parallel components of opposite signs. These differences are evaluated using numerical solutions of the general dispersion relation and shown to exhibit an approximately linear relationship with the parallel electric field near the E region peak altitude of 110 km. An analytic expression for the differences is also derived from an approximate version of the dispersion relation, with comparisons between numerical and analytic results agreeing near 110 km. It is further demonstrated that parallel electric fields do not change the overall symmetry when the full 3‐D wave propagation vector is reversed, with no symmetry seen when either the perpendicular or parallel component is reversed. The present results indicate that moderate‐to‐strong parallel electric fields of 0.1–1.0 mV/m can result in experimentally measurable differences between the characteristics of plasma waves with parallel propagation components of opposite polarity. Key Points: Parallel electric field causes asymmetry in the Farley‐Buneman instability dispersion relation with respect to the aspect angle reversal Explicit analytic expressions are derived that quantify asymmetry for the growth rate and phase velocity near the E region peak of 110 km Asymmetry increases linearly with an increasing parallel electric field near the E region peak, with a nonlinear dependence above 120 km